Réponses

  • Utilisateur Brainly
2014-09-06T14:23:46+02:00
A= (x + 5 )(x + 1)
A= x² + x + 5x + 5
A= x² + 6x + 5

B= (2x - 5)(x + 4)
B= 2x² + 8x - 5x - 20
B= 2x² + 3x - 20

C= (2x - 3)(3x - 8)
C= 6x² - 16x - 9x + 24
C= 6x² - 25x + 24

D= -(1 + 2x)(9x + 1)
D= -(9x + 1 + 18x² + 2x)
D= -(18x² + 11x + 1)
D= - 18x² - 11x - 1
2014-09-06T14:27:23+02:00
A = (x + 5)(x + 1)
A = x² + x + 5x + 5
A = x² + 6x + 5

B = (2x - 5) (x + 4)
B = 2x² + 8x - 5x - 20
B = 2x² + 3x - 20

C = (2x - 3) (3x - 8)
C = 6x² - 16x - 9x + 24
C = 6x² - 25x + 24

D = - (1 + 2x) (9x + 1)
D = - (9x + 1 - 18x² + 2x)
D = - 9x - 1 + 18x² - 2x
D = 18x² - 11x - 1